POLITICAL ECONOMY OF FOOD SYSTEMS: AFRICA AND THE RUSSIA-UKRAINE WAR - NDHLOVU, Emmanuel (Journal of Social Sciences)
This article examines the connection between political developments, economic structures, and food systems in Africa, focusing on the Russia-Ukraine war. The article explores how the prevailing political economy influences food production, distribution, and consumption, identifies the conduits through which the war impacted the food system value chain, and proposes how national and local governments can build resilient food systems capable of meeting the population’s food needs amidst crises. The findings show that the war affected Africa's food system mainly by disrupting the supply chain of commodities that Africa used to develop and sustain its food system. The war disrupted inputs, energy, and food products from Russia and Ukraine to African countries that depend on these countries for these commodities. The article also proposes response mechanisms to the impacts of the war and how African countries can navigate future disruptions and build resilient food systems capable of meeting the population’s food needs. The article could be exciting for politicians and policymakers working on food security, food sovereignty, and diplomatic issues.